Characteristics of Leadership in Private University Organizations in Indonesia: A Conceptual Model [Karakteristik Kepemimpinan Organisasi Perguruan Tinggi Swasta di Indonesia: Sebuah Model Konseptual] - Juliana Murniati (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
Universities (PT) are complex organizations, due to their internal nature and in response to the demands of globalization and technological development. Leaders and leadership are key factors in the success of an organization in fulfilling its goals. Studies on leadership in university organizations (OPT) in Indonesia is still limited, even though leaders perform their functions depending on context. This means that leadership study from different cultures and other organizations (corporations) may not be readily implemented in private university organizations (OPTS) in Indonesia. A qualitative study on 13 leaders of private universities (PTS) aims to identify the leadership characteristics of private university organizations (OPTS); specifically, by portraying leadership functions and leadership styles played by individuals who are active leaders private universities (PTS). The phenomenological qualitative study conducted using grounded analysis presents a conceptual model with three important characteristics: (1) academic leadership; (2) community leadership; and (3) corporate leadership. The interpretation of academic leadership and community leadership relates to the tri dharma (three pillars) of universities (PT), for which the view has not been solidified among the participants at the institutional and individual levels. Meanwhile, from corporate leadership emerges several interpretations related to the adoption of performance-based strategy, succession planning, and qualifications. Facing extremely competitive external challenges, leaders of universities (PT) can consider Systems Theory framework that look at the internal components of organizations holistically, rather than part by part, such that unique leadership characteristics would emerge, such as entrepreneurial leadership with the interpretation of tri dharma that is not merely limited to the dichotomy between research and teaching universities. Perguruan tinggi (PT) merupakan organisasi yang kompleks, baik karena natur internal maupun akibat tuntutan sebagai dampak dari perkembangan teknologi dan globalisasi. Pemimpin dan kepemimpinan merupakan faktor kunci akan keberhasilan organisasi mencapai visinya. Kajian kepemimpinan di organisasi perguruan tinggi (OPT) terutama di Indonesia sangat terbatas, padahal pemimpin berfungsi tergantung pada konteks. Artinya, studi kepemimpinan dari budaya berbeda atau organisasi lain (korporasi) belum tentu dapat diimplementasikan dalam organisasi perguruan tinggi swasta (OPTS) di Indonesia. Studi kualitatif terhadap 13 pemimpin perguruan tinggi swasta (PTS) bertujuan untuk identifikasi karakteristik kepemimpinan di organisasi perguruan tinggi swasta (OPTS); secara spesifik berupa gambaran fungsi pemimpin dan gaya kepemimpinan yang diperankan oleh mereka yang tengah aktif memimpin perguruan tinggi swasta (PTS). Hasil studi kualitatif fenomenologi dengan analisis secara grounded menampilkan model konseptual dengan tiga karakteristik, yakni: (1) kepemimpinan akademik; (2) kepemimpinan komunitas; dan (3) kepemimpinan korporasi. Pemaknaan terhadap kepemimpinan akademik dan kepemimpinan komunitas terkait dengan tri dharma perguruan tinggi (PT), yang pandangannya tidak solid antar partisipan baik pada tataran institusional maupun individual. Sementara pada kepemimpinan korporasi muncul makna terkait adopsi strategi berbasis kinerja, program kaderisasi, dan kualifikasi. Menghadapi tantangan eksternal yang sangat kompetitif, pemimpin perguruan tinggi (PT) dapat mempertimbangkan kerangka systems theory yang melihat komponen internal organisasi secara keseluruhan, bukan bagian demi bagian, sehingga boleh jadi muncul karakteristik kepemimpinan yang unik seperti entrepreneurial dengan pemaknaan terhadap tri dharma yang tidak terbatas pada research atau teaching university semata.